A preliminary study of knowledge, attitude and practices of pesticide use among oil palm workers in Johor - Mior Iskandar, Siti Nazhatul Marina; Leman, Abdul Mutalib; Baharudin, Mohd Rafee; Masripan, Roslizan; T., M. Faazir; A., M. Ifwat (EDP Sciences, 2016)
Agricultural sector is a fundamental activity that has been practiced since the civilization of Babylonian, which also has been proven by the glory of Nile River Valley and Mekong Valley. History has shown that the migration of investors and foreign labors in Malaysia in 1960 was to be harvested fortune from the land due to its fertility and suitability. As a developing country, agriculture is one of the important sectors in Malaysia that contributes towards the national economy development. The mentioned sector has indirectly provided benefits both local and global perspectives either in terms of business opportunity as well as employment opportunity. In general, this study aims to assess the level of knowledge, practices and attitudes in the use of pesticides in oil palm plantation workers in Johor. The findings of this study will be used as reference in the farming industry, particularly for the awareness and understanding of good farm management practices and safety for agricultural workers by providing information regarding precautionary measures. This study will engage oil palm workers in Johor which are tasked to carry out pesticides handling activities. A total of 138 respondents were selected for the study. The methodology approaches that will be used in this study are questionnaire and interview. The results of this study will be used as reference in the farming industry, particularly the awareness and understanding of good farm management practices and safety for agricultural Workers By Informing Them Of A Precautionary Measure.